Analysis of documents from the database on documentary control of indigenous ethnic groups in Costa Rica 1979-2003 - Álvarez Hernández, Esteban (2010)
This article shows how a referential database makes it possible to obtain important data with which conclusions can be reached that in some cases surprise. In order to carry out this study, the following fields of the Database on Documentary Control of Indigenous Ethnic Groups of Costa Rica 1979-2003 were used: author, place of publication, publisher, year, language and support. The analyzed database has two thousand records and was developed in the Winisis program. In addition, it shows the application of different methods to learn more about scientific production such as: the Price Index, the Collaboration Index.